LITERASI KEUANGAN : SUATU KAJIAN ANALISIS PENGARUH TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA UNIVERSITAS TIMOR - Seran, Marisa; Andre Pattipeilohy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Financial literacy is very necessary especially for millennials who are in college.This will be a provision for them later to be able to manage well every financial theyhave, so as to meet their every need of life. This study analyzes the Effect of FinancialLiteracy on Student Personal Financial Management. The sample in this study wasan active student who was at the University of Timor as many as 461 students. Theresults showed that Financial Knowledge partially influenced the PersonalFinancial Management of University of Timor Students. Financial Skill partiallyaffects the Personal Financial Management of University of Timor Students.Financial Knowledge partially affects the Personal Financial Management ofUniversity of Timor Students. Financial Knowledge, Financial Skill and FinancialConfidance simultaneously affect the Personal Financial Management of Universityof Timor Students.. Financial Skill has a more dominant influence (compared toFinancial Knowledge and Financial Confidance)on Personal FinancialManagementof University of Timor Students